Analytical Study of Experiential Learning: Experiential Learning Theory in Learning Activities - Rahmi, Wifqi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The aim of this research is to describe experiential learning in learning activities. David A. Kolb's Learning Theory highlights four keys stages: experience, reflection, abstract concepts, and active experimentation. This research is a library research or literature review, primarily focus on collecting and reviewing various previous studies on Kolb's learning theory. The findings indicate that the four stages of experiential learning models can enhance student engagement, deepen understanding of subject matter better, develop critical and creative skills to face future challenges, and foster collaborative work, and it can be effectively implemented at all levels of education. It can be concluded that learning activities using the experiential learning model can encourage student involvement to achieve maximum learning outcomes, and can be used at all levels of education while still paying attention to elements of relevance of the material and learning environment. However, there are still several shortcomings and challenges in applying this theory, particularly in terms of resource readiness.